Collateral and local lending: Testing the lender-based theory - Andrea Bellucci; Alexander Borisov; Germana Giombini; Alberto Zazzaro (Institut für Angewandte Wirtschaftsforschung (IAW), 2015)
In this paper we empirically test the recent lender-based theory for the use of collateral in bank lending. Based on a proprietary dataset of loan contracts written by a local bank in competitive credit markets, we use the physical proximity between borrowers and the lending branch of the bank to capture its information advantage and the magnitude of collateral-related transaction costs. Overall, our results seem more consistent with several classic borrower-based explanations rather than with the lender-based view. We show that, conditional on obtaining credit from the local bank, more distant borrowers experience higher collateral requirements and lower interest rates. Moreover, competitive pressure from transaction lenders does not magnify the importance of lender-to-borrower distance. Our findings are also obtained with estimation techniques that allow for endogenous loan contract terms and joint determination of collateral and interest rates.
Keywords: G21; G32; L11; 330; Distance; Collateral; Interest Rate; Bank lending